Can Bioethanol Lead Pakistan Towards Sustainability and Prosperity? A Narrative Review - Mohsin, Abeer; Fatima, Syeda Zehratul (Journal of Technology Innovations in Renewable Energy, 2019)
Economic recession, power and fuel shortage, waste management and pollution leading to global warming and climate change are few of the major issues faced by Pakistan, a developing country. These issues can be addressed to some extent by implementing policies and programmes by the government that will promote the development of the renewable energy sector in the country. Pakistan being an agricultural country has great potential to produce bioethanol, by using agricultural and municipal waste, and be able to fulfil its fuel requirements. Countries such as Canada, China and Brazil, the top producers of bioethanol in the world, can be followed as examples in terms of making policies for the growth and development of bioethanol industries. The government should make policies to replace traditional petroleum with ethanol-blended fuel to minimize the energy crisis and environmental pollution throughout the country. Keywords: Renewable energy, pollution, economic growth, sustainable development goals, global warming, waste management.